Sn–31Bi–19In alloy: A golden ratio design for exceptional elongation, high strength, and low-temperature soldering - Yu-An Shen; Chih-Hsiang Liu; Hao-Zhe Kao (Journal of Materials Research and Technology, 2025)
Advanced semiconductor packaging demands low-temperature soldering and high soldering strength to mitigate thermal warpage challenges. This study developed the mechanical, thermal, and soldering properties of a novel Sn–Bi–In low-temperature alloy (LTA), designated as SBI3119, with a composition of 50:30.9:19.1, inspired by the golden ratio, and evaluated its mechanical, thermal, and soldering properties. Tensile testing revealed an ultimate tensile strength (UTS) of 41.5 MPa and an exceptional elongation of 263 %, classifying SBI3119 as a room-temperature super-elongation LTA. The alloy exhibited an optimal balance of strength and ductility, attributable to its golden ratio-based design. Moreover, SBI3119 demonstrated a low transition temperature of 76 °C, a melting temperature of 150 ° C, excellent wettability (206 % spreading), and the formation of a thin Cu6(Sn, In)5 intermetallic interlayer when soldered with Cu. This facilitated successful soldering at 160 ° C and achieved a high soldering strength of 43.4 MPa. These findings suggest that SBI3119 is a promising candidate for advanced semiconductor packaging that requires high strength, ductility, and low-temperature soldering.